2008
DOI: 10.1248/cpb.56.1229
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Interaction between Andrographolide and Glutathione Follows Second Order Kinetics

Abstract: The intracellular level of glutathione (GSH) was significantly decreased after the addition of andrographolide (1) to cell cultures of HepG2. When the molecular interaction between andrographolide and GSH was investigated under a condition mimicking the in vivo environment, we observed that the level of GSH dropped in the presence of andrographolide. Stoichiometric analysis indicates that the reaction between these two reactants was 1 to 1 at pH 7 and followed second order kinetics. The activation energy of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
9
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 19 publications
5
9
0
Order By: Relevance
“…This observation suggested that Andro alone at this concentration (20 µM) may disturb the proper formation of mitotic spindles in the cells. We have shown that Andro alone can induce DNA damage by altering the redox states in cells [16], [31]. The formation of small dot-shaped chromosomes may be due to limited DNA damage induced by Andro, which is consistent with the finding that during apoptosis, DU145 cells do not form DNA ladders typical of other apoptotic cells but instead form DNA fragments that are 50 kb long (51).…”
Section: Resultssupporting
confidence: 68%
“…This observation suggested that Andro alone at this concentration (20 µM) may disturb the proper formation of mitotic spindles in the cells. We have shown that Andro alone can induce DNA damage by altering the redox states in cells [16], [31]. The formation of small dot-shaped chromosomes may be due to limited DNA damage induced by Andro, which is consistent with the finding that during apoptosis, DU145 cells do not form DNA ladders typical of other apoptotic cells but instead form DNA fragments that are 50 kb long (51).…”
Section: Resultssupporting
confidence: 68%
“…There are reports that ANDRO may directly react with thiol of GSH in vitro, and the assumed hypothesis is that the α,β-unsaturated lactone moiety of ANDRO can react with GSH through the Michael addition reaction. 16,22 The results illustrated in Figure 2B also confirmed the potential existence of the direct reaction of ANDRO with GSH in vitro. BSO is a well-known inhibitor of GSH synthesis, and it has been reported that pretreatment with BSO augments the hepatotoxicity of many chemicals, which can be detoxified by GSH.…”
Section: Discussionsupporting
confidence: 67%
“…S1 and S2B-D). Auranofin is a bulky molecule, known to alkylate active protein thiols (or selenols such as in thioredoxin reductase) by a ligand-exchange mechanism, the so-called sulfhydryl shuttle (29), while andrographolide, a labdane diterpenoid recently patented for the treatment of Amyotrophic Lateral Sclerosis and other neurodegenerative disorders (UK Patent application GB2464813), has an a,b-unsaturated lactone moiety alkylating protein or peptide-active -SH or -NH2 groups by Michael addition followed by dehydration (53). The observed lag-periods for TP may be interpreted as a switch in the ratelimiting step, meaning that there is a step preceding their direct alkylation of Keap1 reactive cysteines.…”
Section: Discussionmentioning
confidence: 99%